The mental image of vocational education for tenth grade students in public schools in Tulkarem Governorate - Iter, Nuha Ismail; Hijaz, Alaa Mahmoud (Journal of Educational and Psychological Sciences, 2023)
The mental image of vocational education is a mental attempt in which the student reconstruction of the vocational education concept from his memory using cognitive, emotional, and practical component, this study tried to reveal the nature of the mental image of tenth grade students in public schools in Tulkarem Governorate. The descriptive analytical method was used, and the study was applied to an available sample of tenth grade students in Tulkarem Governorate, consisting of (445) male and female students. A questionnaire was used, it was consisted of the student’s personal and environmental variables, and (18) items of the three study components (cognitive, emotional, and practical component), the appropriate statistical analysis was used for descriptive studies, the study reached a set of results, most notably: the degree of the total score, the emotional component, and the practical component of the mental image of vocational education among the tenth grade students came at an average level. While the cognitive component was at a high level, there was no effect for the variables of gender, place of residence, source of information, mother’s work and father’s work on the mental image of vocational education for tenth grade students, while there was an effect of school average variables and came in favor of the rates from (50-89) ), for family income and in favor of low income, and the educational level of the mother of the father and in favor of the educational level is less than a bachelor’s. The study recommends the necessity of introducing students to vocational education from the first grades, activating various and modern sources of information on vocational education, and conducting experimental, and comparative studies on the mental image of vocational education.